Pemanfaatan Reclaimed Asphalt Pavement (RAP) Sebagai Bahan Tambahan Perkerasan Jalan Type Asphalt Concrete-Wearing Courese (AC-WC) - Mukhammad Khafid Zakiya Alwi; Mochamad Ridwan (Jurnal Sains dan Teknologi (JSIT), 2023)
The focus of this research is on usageReclaimed Asphalt Pavement (RAP) as a road pavement additiveAsphalt Concrete Wearing Course (AC-WC). In this research, a case study was conducted at Jalan Totok Kerot, Temenggungan, Bakung Temenggung, Balongbendo District, Sidoarjo Regency. This research was conducted by analyzing the RAP which will be substituted with additional aggregate materials needed in accordance with the provisions of the 2010 Ministry of Public Works (Revision 3). In this study, aggregate testing (coarse, fine,filler) as well as testing of the mixture using the Marshall test. This study aims to determine the asphalt content and the type of aggregate contained in the RAP obtained from Jalan Totok Kerot Temenggungan, Bakung Temenggung, Balongbendo District, Sidoarjo Regency. In addition, this study also aims to obtain the optimum composition of the mixture of RAP materials and new materials according to the combined aggregate gradation in the 2010 General Highways Specifications (Revision 3).